UNLEASHING MEDICAL TOURISM IN BANDUNG: OPPORTUNITIES, CHALLENGES, AND STRATEGIC INTERVENTIONS FOR GROWTH - Siswanto, David Jefry; Wahyoedi, Soegeng; Saparso, Saparso (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The global demand for medical tourism is on the rise, and Indonesia is poised to enter this market by leveraging its tourism capabilities. Bandung, the capital of West Java, is identified as a city with significant potential for cultivating this sector. This study seeks to explore, comprehend, and detail the possibilities for, and the actualization of, medical tourism in Bandung, alongside identifying the challenges faced during its implementation. A qualitative, descriptive research methodology has been employed to achieve these objectives. The author found that Bandung City is a city category that has high potential in the development of medical tourism and has the potential to increase the tourism sector that can support the improvement of health services. The development of medical tourism can increase GRDP growth by implementing collaboration between stakeholders based on the penta helix model. The potential of the tourism sector in Bandung City is scattered, such as shopping, culinary and education-based tourism. This can be in line with the growth of health facilities in Bandung City. To maintain the stability of this growth, there needs to be collaboration between stakeholders. Obstacles in the implementation of medical tourism in Bandung City are uneven health facilities and human resources, lack of international language usage and lack of publicity and promotion. Suggestions for the potential and application of medical tourism in Bandung City are the development of tourism infrastructure and facilities in the form of accessibility and amenity of tourist attractions and health facilities that support medical tourism programs need to be improved.